Electronic structure and band gap of oxygen bearing c‐Zr3N4 and of c‐Hf3N4 by soft X‐ray spectroscopy. Issue 4 (27th December 2013) - Yablonskikh, Mikhail; Dzivenko, Dmytro; Bourguille, Judith; Riedel, Ralf; Magnano, Elena; Parmigiani, Fulvio; Zerr, Andreas
<x xml:space="preserve">Abstract</x> Electronic band structures of two novel semiconducting nitrides of the group‐IV elements of Th3P4‐type crystal structure, c‐M3N4, where MZr or Hf, is investigated using an element specific soft X‐ray spectroscopy for the first time. From the pairs of N 1s X‐ray absorption and N 2p → 1s resonant X‐ray emission spectra partial densities of states (PDOS) of nitrogen, predicted to be strongly hybridized with those of the metals, are obtained for both compounds. From these data the electronic band gaps of oxygen bearing c‐Zr3N4 and of c‐Hf3N4, predicted before to be direct or nearly direct, are derived to be Eg = 1.6 eV and Eg = 1.8 eV, respectively. While the experimentally determined Eg for c‐Hf3N4 agrees with the theoretical one obtained using the local density approximation (LDA) method, the Eg measured for oxygen bearing c‐Zr3N4 is significantly higher than those calculated using both the LDA and the generalized gradient approximation method. The examined compounds, having high hardness, elastic moduli and oxidation resistance, appear to be multifunctional materials suitable also for applications as (opto)electronic materials. <inline-graphic xlink:href="ark:/27927/pgg55088p6q" content-type="pssa201330338-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> Band gap evolution in c‐M3N4 nitrides as a function of the cation type, Zr or Hf.